MUTATIONS IN 1700 BP FRAGMENT OF RPOB GENE OF MULTI-DRUG RESISTANT MYCOBACTERIUM TUBERCULOSIS ISOLATE - Yowani, Chandra; Sukardika, I K.; Mantik-Astawa, I N.; Junitha, I K. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol 6 No 2 (2012): Indonesian Journal of Biomedical Sciences, 2013)
This research aimed to amplify a 1700 bp fragment of rpoB gene of multidrug resistance M. tuberculosis (MDR-TB) isolate and determine types of mutation beyond the core region (hot-spot region). DNA sequencing studies indicate that more than 95% of rifampin-resistant M. tuberculosis strains have mutations within the 81-bp hot-spot region (codons 507 to 533) of the RNA polymerase ?-subunit (rpoB). Since almost 90 % of rifampicin resistant isolate are also resistant to isoniazid, mutation in rpoB gene become important as a surrogate marker for MDR-TB. MDR- TB isolates used for this research, namely isolate 885, was collected by Regional Health Laboratory of Surabaya. PCR was used to amplify the gene, on described steps : a cycle of preheating at 95°C for 15 minutes, amplifying in 45 cycles ( 1 minute at 94°C, 1 minute at 58°C, 1 minute 72°C) and post extension for 5 minutes at 72°C. The mutations were detected by sequencing and alignment using MEGA4. The result of this research showed that there were new mutations downstream of the core region of rpoB. Sequence analysis showed some mutations such as S594A, S626V, T629A. In conclusion, it is reported for the first time, new mutations at downstream region of the core region of rpoB.
Keywords: M.tuberculosis; rifampicin resistance; MDR-TB